Gulliver's travels - Swift, Jonathan, 1667-1745.; Small, David, 1945- (London : Penguin Books, 1994)
On two voyages, an Englishman becomes shipwrecked in a land where people are six inches high, and stranded in a land of giants.
7.5
5-8.
Keywords: Fantasy; Size -- Fiction; Size and shape -- Fiction; Fantastic fiction